Visualizing dynamic microvillar search and stabilization during ligand detection by T cells. - Cai, E; Marchuk, K; Beemiller, P; Beppler, C; Rubashkin, MG; Weaver, VM; Gérard, A; Liu, TL; Chen, BC; Betzig, E; Bartumeus, F; Krummel, MF (American Association for the Advancement of Science, 2017)
During immune surveillance, T cells survey the surface of antigen-presenting cells. In searching for peptide-loaded major histocompatibility complexes (pMHCs), they must solve a classic trade-off between speed and sensitivity. It has long been supposed that microvilli on T cells act as sensory organs to enable search, but their strategy has been unknown. We used lattice light-sheet and quantum dot-enabled synaptic contact mapping microscopy to show that anomalous diffusion and fractal organization of microvilli survey the majority of opposing surfaces within 1 minute. Individual dwell times were long enough to discriminate pMHC half-lives and T cell receptor (TCR) accumulation selectively stabilized microvilli. Stabilization was independent of tyrosine kinase signaling and the actin cytoskeleton, suggesting selection for avid TCR microclusters. This work defines the efficient cellular search process against which ligand detection takes place.